Direção de Documentário - Rabiger, Michael (Elsevier Editora, 2012)
Directing the Documentary is a comprehensive manual that has inspired over 100,000 readers worldwide. If you are interested in making documentary films, everything you need technically and conceptually is here. Filled with practical advice on every stage of production, this is the book you will return to throughout your career. Directing the Documentary covers the methods, technologies, thought processes, and judgments that a director must use throughout the fascinating process of making a film. It emphasizes low-cost digital techn.